Hybrid Position-Based and DTN Forwarding for Vehicular Sensor Networks. (5th April 2012) - Li, Fan; Zhao, Lei; Fan, Xiumei; Wang, Yu
Abstract : Efficient data delivery in vehicular sensor networks is still a challenging research issue. Position-based routing protocols have been proven to be more suitable for dynamic vehicular networks or large-scale mobile sensor networks than traditional ad hoc routing protocols. However, position-based routing assumes that intermediate nodes can always be found to set up an end-to-end connection between the source and the destination; otherwise, it suffers from network partitions which are very common in vehicular networks and leads to poor performances. This paper addresses data delivery challenge in the possible intermittently connected vehicular sensor networks by combining position-based forwarding strategy with store-carry-forward routing scheme from delay tolerant networks. The proposed routing method makes use of vehicle driving direction to determine whether holding or forwarding the packet. Experimental results show that the proposed mechanism outperforms existing position-based solutions in terms of packet delivery ratio.